"Człowiek dążący", czyli antropologia filozoficzna w twórczości Krystiana Lupy. Analiza zjawiska na podstawie wybranych spektakli - Merk, Sylwia (Załącznik Kulturoznawczy, 2019)
The starting point of Krystian Lupa’s work seems to coincide with the postulate that funds philosophical anthropology – get to know yourself. For the director, cognition is a kind of process, a constant study of himself and a constant verification of his status in the world. Lupa considers the striving for understanding to be the essence of humanity. The central issue of his work is therefore the ‘seeking man’. This study outlines the philosophical context of the director’s work, and also exposes in its context such problems as: the status of carnality, sexuality and eroticism, the question of utterance, and the meaning of unconsciousness and dreams in art. These reflections are subordinated to the extraction of anthropological motifs in Lupa’s investigations, as well as to the explanation of the concept of ‘the seeking man’.